PENERAPAN KODE ETIK PROFESI TERHADAP PROFESIONALISME GURU DI INDONESIA - Salsabila, Sabina Naghma; Dewi, Mutiara; Aeni, Siti Nurul; Nida, Siti Solehatun; Kholifah, Siti (Jurnal Anak Bangsa, 2025)
Learning in early childhood requires innovative learning media to optimize its development, Quality education requires skilled teachers who not only impart knowledge but also serve as role models for their students. Teachers are responsible not only for educating and sharing their knowledge but also for guiding students by setting a positive example. In addition to teaching, teachers must protect, train, evaluate, and supervise students within the educational environment while adhering to an established code of ethics. One of the most important frameworks for fulfilling the duties and responsibilities of the teaching profession is the professional code of ethics. A code of ethics helps teachers enhance their academic qualifications, prepare for lessons effectively, and act impartially and without discrimination. This study seeks to explain the importance of understanding and enforcing a code of ethics to improve teacher professionalism, using a literature review research methodology. The findings indicate that implementing a teacher code of ethics positively impacts student learning outcomes, enhances teacher professionalism, and improves overall education quality. The effectiveness of implementing a teacher code of ethics is influenced by several factors, including education, supervision, organizational culture, and school leadership.varied.